Detection and evaluation of cracks in the concrete buffer of the Belgian Nuclear Waste container using combined NDT techniques. (1st March 2015) - Iliopoulos, S.; Aggelis, D.G.; Pyl, L.; Vantomme, J.; Van Marcke, P.; Coppens, E.; Areias, L.
Highlights: The simultaneous and combined application of DIC, AE and UPV NDT techniques improves cracking monitoring. The techniques were applied on a scaled model of the Belgian Nuclear Waste container. Full characterization of the cracks (onset, width, depth, development) was achieved. Abstract: The long term management of high-level and heat emitting radioactive waste is a worldwide concern, as it directly influences the environment and future generations. To address this issue, the Belgian Agency for Radioactive Waste and Enriched Fissile Materials (ONDRAF/NIRAS) has come up with a reference design for the geological disposal of this waste. In this design the wastes are first post-conditioned in a massive concrete structure called Supercontainer (SC) before being transported to an underground repository. The feasibility to construct this structure is being evaluated through a number of scaled models that are tested using various measurement techniques. This paper reports on the onset and evolution of the observed cracking of the concrete structure obtained by simultaneously applying Digital Image Correlation (DIC), Acoustic Emission (AE) and Ultrasonic Pulse Velocity (UPV) nondestructive testing techniques. In particular, the results highlight the time of onset and location of crack initiation as well as the width and depth of the cracks. Finally, emphasis is given to AE indices which indicate the severity of the cracks.